Parallels between UNUSUAL FLORAL ORGANS and FIMBRIATA, genes controlling flower development in Arabidopsis and Antirrhinum. - Ingram, G C (1995)
The unusual floral organs (ufo) mutant of Arabidopsis has flowers with variable homeotic organ transformations and inflorescence-like characteristics. To determine the relationship between UFO and previously characterized meristem and organ identity genes, we cloned UFO and determined its expression pattern. The UFO gene shows extensive homology with FIMBRIATA (FIM), a gene mediating between meristem and organ identity genes in Antirrhinum. All three UFO mutant alleles that we sequenced are predicted to produce truncated proteins. UFO transcripts were first detected in early floral meristems, before organ identity genes had been activated. At later developmental stages, UFO expression is restricted to the junction between sepal and petal primordia. Phenotypic, genetic, and expression pattern comparisons between UFO and FIM suggest that they are cognate homologs and play a similar role in mediating between meristem and organ identity genes. However, some differences in the functions and genetic interactions of UFO and FIM were apparent, indicating that changes in partially redundant pathways have occurred during the evolutionary divergence of Arabidopsis and Antirrhinum.